THE CLINICAL, EPIDEMIOLOGICAL AND MICROBIOLOGICAL PATTERN OF COMMUNITY-ACQUIRED PNEUMONIA IN THE KARACHAY-CHERKESS REPUBLIC - Palina Khalitovna Katchieva; Marat Borisovich Uzdenov; Sergey Mikhaylovich Kotelevets (Современная наука и инновации, 2022)
The article discusses the epidemiological situation in the pathology of Respiratory in dynamics for five years, the role of community-acquired pneumonia in mortality from respiratory disease, spectrum of microorganisms most characteristic of community-acquired pneumonia and factors distorting the microbiological picture.